Motion sickness countermeasures for autonomous driving - Pereira, Eduarda (2024)
Funding Information: This work is supported by FCT – Fundação para a Ciência e Tecnologia within the R&D Units Project Scope: UIDB/00319/2020. IL was (in part) supported by the Center of Technology and Systems (CTS) UIDB/00066/2020 and IL and ES by a BIAL funded project (PT/FB/BL-2022-231). The authors would also like to thank the European Structural and Investment Funds in the FEDER component, through the Operational Competitiveness and Internationalization Programme (COMPETE 2020) [Project No. 039334; Funding Reference: POCI-01-0247-FEDER-039334] for supporting this study and the Grants of EP, HM, IL, ES. Publisher Copyright: © 2023